Pengaruh Islamic Leadership terhadap Produktivitas Kerja Karyawan PT. Amaan Indonesia Sejahtera Pasean - Adawiyah, Yuliatul; Habibi, Azwar (Sekolah Tinggi Ilmu Syariah (STIS) Ummul Ayman Pidie Jaya, Ace, 2025)
In the era of globalization, competition among companies is becoming increasingly fierce, indicating that companies are required to continuously improve their work productivity in order not to fall behind the times. Human Resources (HR) are considered one of the important factors in a company's success. Additionally, Human Resources play an active role in the continuity of the company's activities because they possess a lot of potential that can drive the achievement of the organization's goals. Islamic leadership is leadership based on the Quran and Hadith, where the principles of Islamic leadership include the principles of ideal leadership. Islamic leadership in a company is derived from Islamic sources, which are then implemented in the company thru Islamic practices and beliefs. This research aims to determine and analyze the influence of Islamic leadership on employe work productivity at PT Aaman Indonesia Sejahtera. Islamic leadership is a leadership concept that refers to Islamic principles such as trustworthiness, justice, honesty, and moral and spiritual responsibility in leading. In the context of the workplace, leadership based on Islamic values is believed to be able to create a harmonious work environment, increase employe motivation, and encourage the achievement of optimal productivity. PT Aaman Indonesia Sejahtera, as a company that upholds Islamic values, serves as a relevant object to observe the extent to which the implementation of Islamic leadership impacts the performance and productivity of its employes. This study uses an associative quantitative approach. With a sample of 37 respondents. The research results are as follows: based on t-counting, which is 19.822 > t-table 1.687 with a significance level of 0.000 < 0.05, Islamic Leadership has an impact on the work productivity of employes at PT Aaman Indonesia Sejahtera. In addition, the coefficient of determination test showed an Adjusted R Square value of 0.916. This illustrates that the independent variable (Islamic Leadership) can explain the dependent variable (Employee Productivity) by 91.6%. Meanwhile, the remaining (100%-91.6%= 8.4%) is explained by other variables that were not examined in this study.